PENGARUH PENAMBAHAN PHENOL FORMALDEHID TERMODIFIKASI NATRIUM SILIKAT TERHADAP LEM SEPATU BERBASIS KARET - M.W. Syabani; Indri Hermiyati; R.L.M.S. Ari Wibowo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2014)
This research aim are to studying adhesion characteristic of shoes adhesive, ie viscosity, tack and peel strenght. Shoes adhesive made from natural rubber and synthetic rubber (SBR) with toluene as the solven. SRB composition in the mix are 0, 20, 40, 60, 80 and 100% weight. Three variation of phenol formadehyde composition are 40, 80 and 120 per hundred parts of rubber (phr). The results show us that the viscosity lower as the % SBR added is higher, and the loop tack has the highest value at 20% SBR added. The peel tack has highest value at 60% SBR added for three peel test model, except on the control sample. For every same % SBR composition, adhesive sample that has 40 phr phenol formaldehyde composition, gives higher loop tack and peel strenght value. We can conclude from this results that adhesive with 40% phenol formaldehyde composition will give optimum wettability from adhesive to substrat.